2020
DOI: 10.1186/s12951-020-00612-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and in vitro–in vivo evaluation of bortezomib supermolecular aggregation nanovehicles

Abstract: Backgrounds: Intolerable toxicity and unsatisfactory therapeutic effects are still big problems retarding the use of chemotherapy against cancer. Nano-drug delivery system promised a lot in increasing the patients' compliance and therapeutic efficacy. As a unique nano-carrier, supermolecular aggregation nanovehicle has attracted increasing interests due to the following advantages: announcing drug loading efficacy, pronouncing in vivo performance and simplified production process. Methods: In this study, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…BTZ has a cytotoxic effect in a variety of tumor cells 21 and can reduce the therapeutic concentration of tumor necrosis factor-related apoptosis-inducing ligand, for treating GBM 22 . To determine whether BTZ reduces the concentration of CPX required for its effects in GBM cells, we combined BTZ with CPX to treat U251 and SF126 cells.…”
Section: Resultsmentioning
confidence: 99%
“…BTZ has a cytotoxic effect in a variety of tumor cells 21 and can reduce the therapeutic concentration of tumor necrosis factor-related apoptosis-inducing ligand, for treating GBM 22 . To determine whether BTZ reduces the concentration of CPX required for its effects in GBM cells, we combined BTZ with CPX to treat U251 and SF126 cells.…”
Section: Resultsmentioning
confidence: 99%
“…ADSCs were incubated in the solution (5 μL of annexin V-mCherry and 1 μL of GreenNuc™ caspase-3 substrate per 200 μL of binding buffer) for 30-45 min at 37°C without light. Cell membrane permeability Caspase-3 Substrate GreenNuc™ for the detection of caspase-3 activity in cultured cells can be used for real-time monitoring [ 26 ]. Immunofluorescence microscopy was used to obtain images (GreenNuc™, excitation/emission: 500/530 nm; Annexin V-mCherry, excitation/emission: 587/610 nm).…”
Section: Methodsmentioning
confidence: 99%
“…However, in vivo experiments showed that mice treated with BTZ alone were characterized by weight loss while the pVP coated BTZ-NPs led to weight gain in mice. This phenomenon indicated the reduced systemic toxicity of the BTZ-NPs [ 83 ].…”
Section: Pvp In Micro- and Nano Drug Delivery Systemsmentioning
confidence: 99%
“…( c ) Antidegradation action of pVP. Adapted with permission from [ 83 ], Springer, 2020. ( d ) Scheme of the action of nanoparticles obtained by two different methods, and graph showing enhancement of cisplatin toxicity through increased intercellular accumulation of drug bonded with NP compared to free cisplatin (*—statistically significant difference ( p < 0.05) from free cisplatin, **—statistically significant difference from M2-NPs).…”
Section: Figurementioning
confidence: 99%